Soya protein antibodies in man: their occurrence and possible relevance in coeliac disease. Issue 3 (March 1982) - Haeney, M R; Goodwin, B J; Barratt, M E; Mike, N; Asquith, P
Abstract : Circulating antibodies to soya-derived protein antigens have been measured in patients with duodenitis, Crohn's disease, ulcerative colitis and coeliac disease. Significantly raised antibody titres were found frequently in the coeliac group, particularly those patients showing a suboptimal response to a gluten-free diet, but rarely in subjects with other gastrointestinal diseases. Antisoya activity was not necessarily accompanied by antibodies to other common dietary antigens. We suggest that some coeliacs may have an associated dietary soya sensitivity which could adversely influence their response to gluten withdrawal.